Position and speed optimization of servo motor control through FPGA - Ajel, Ahmed R.; Abdul Abbas, Huda M.; Mnati, Mohannad Jabbar (Institute of Advanced Engineering and Science, 2021)
We have put our model in this paper in which we will be controlling the speed and direction of the servomotor through FPGA. So, as to guarantee the precision from the check control procedure, we have made a project in which the document provides the control plane associated with servo motor depending on Altera DE1 board gentle primary processor as program controller. The system utilizes FPGA since the primary gadget, as well as within Quartus II 10.0 program atmosphere. The associated control components aremade to type a good executable control program in which speed and direction will be controlled the servo motor performance. The particular handle signs from your handle method are usually separated and amplified which results in the push to appreciate the particular handle with the servo motor. Based on the features associated with Altera, it is expounded through 2 facets of equipment’s hardware as well as a software program that supplies an answer for that style associated with the servo control system. This particular document utilizes the actual PID control formula to manage the actual common screening device to attain versatile as well as precise control reasons. The actual equipment execution from the PID control formula is put in place through FPGA; precise as well as effective control program is built to enhance the speed and performance of the servomotor through FPGA.